The Counseling Activity of Girlhood for University Students of Universitas Singaperbangsa Karawang - Medi Nopiana; Rina Maria Hendriyani; Novian Ekawaty (Universitas Negeri Semarang, 2026)
The community service activity was motivated by the community service team's concern about the rampant promiscuity that is plaguing Indonesia's young generation today, primarily among university students. Therefore, lecturers need to provide religious-based moral guidance to students, particularly students of Universitas Singaperbangsa Karawang, based on the mandate given to lecturers to educate them while they are on campus. Based on this, the community service team carried out a girlhood community service activity for female students of the university, mainly Muslim female students. The activity was held offline on Monday, November 3, 2025. The method of implementation of the activity employed a counseling method. The community service activity provides significant benefits for female students, especially opening up their insights in preparing them to build their households in the future. This activity is expected to be carried out periodically by organizing larger events, reaching all female students at Universitas Singaperbangsa Karawang.